Benjamin Thompson (Conde Rumford) e o experimento da radiação do frio - Alves, Eliade Amanda (2013)
This work has the purpose to understand the role of experiment in constructing knowledge. Here we have analyzed the radiation of cold experiment performed by Rumford in 1802 and its theoretical implication concerning the heat. Regarding this we reviewed some Rumford s early studies which led us to a better understanding of his trajectory until he could perform his experiment. We can say that the hypothesis adopted by Rumford related to the nature of heat determined decisively the interpretation given by him to the experiment results. We consider here original texts published by Rumford, specially An Experimental Inquiry Concerning the Source of Heat Which is Excited by Friction in which he described his radiation of cold experiment. Through this study we concluded that although experiments results are very important for the construction of knowledge, they are not sufficient to validate or refute a hypothesis definitely